(untitled) (Advances in Civil and Architectural Engineering, 2021)
In current codes and guidelines for pedestrian bridge design, the vibration serviceability requirement is determined as a pedestrian comfort criteria, by assessing the maximum acceptable acceleration of any part of the bridge deck, but these criteria can also be defined as the maximum acceptable deflection or velocity at the most unfavorable part of the bridge deck. The design models of dynamic pedestrian load for serviceability limit state (SLS) verification are based on experimental models of dynamic pedestrian load; however, design models of vertical pedestrian load omit the static component of pedestrian weight. In this study, we compare the dynamic responses of different single-span bridge decks, each with a resonance frequency of 2 Hz. We show that omitting the static component is appropriate when defining the comfort criteria by using the maximum acceptable bridge deck velocity or acceleration.